A Study with Simulation of Range Free Localization Techniques in Wireless Sensors Networks - Mehannaoui, Raouf; Mouss, Nadia-Kenza (International Conference on Advanced Electrical Engineering (ICAEE), 2019)
Wireless sensors networks are used in several fields of application, in most applications, knowing the location of the sensors nodes is necessary. According to the distribution of the calculations on sensors nodes, the localization techniques are classified into two techniques: centralized and decentralized (distributed). Distributed localization techniques can be classified into two categories: range free and range based. DV-HOP is a range free simple localization algorithm, but it has low localization accuracy, despite the improvements of the proposed DV-Hop algorithms. Maintaining a balance between a high location accuracy and good stability and simplicity is always a challenge. In this article, we have focused our study on the localization algorithm range free DV-HOP, the study is based on the accuracy error which is the most important factor in the localization. To better study the DV-HOP algorithm, we implemented DV-HOP using MATLAB. The purpose of this article is to present Range Free localization techniques and open up a perspective of proposing new localization techniques in wireless sensors networks.